Exploring the resilience of ICU medical social workers in Singapore's end-of-life care settings - Tan, Xavierlyn Zi Jie (Nanyang Technological University, 2020)
The Intensive Care Unit (ICU) is known for its higher mortality rates relative to other wards in a hospital. Apart from having greater exposure to deaths, ICU healthcare professionals also experience high occupational stresses and are more vulnerable to burnout. For ICU medical social workers, this issue is exacerbated by unique challenges such as the lack of death education and hospital guidelines which can impact their ability to offer appropriate psychosocial support. Despite these difficulties, many ICU medical social workers have demonstrated resilience in the face of these difficulties. The present study aimed to explore the resilience of ICU medical social workers in Singapore. Semi-structured interviews were conducted with four participants. Transcripts were analysed using framework analysis which revealed four main factors which contributed to the resilience of ICU medical social workers: interpersonal intelligence, safe and communicative work environment, learning through experience and intrapersonal contributors. These findings and their implications were discussed.